The Potential of Agriculture and Forestry Biomass Wastes As Source of Bioenergy - . Hardoyo (Bandar Lampung University (UBL), 2013)
Indonesia as a agriculture country has very much of agriculture and forestry biomass-wastes. Until now, that biomass wastes were sold out without some treatment to produce the higher value product. The agriculture and forestry biomass-wastes contain lignocelluloses material that have 3 groups carbohydrate structure : cellulose, hemicellulose and lignin. That material were potentially to treat to product ethanol that can use as new and renewable energy. It is important, the use of agriculture and forestry biomass-waste did not over-lap with food and feed programe and also support the national energy strategy and green energy concept. Technology convertion of biomass-waste to product bioenergy could be done by physic, chemical and biologically. To enhance the sustainability of the world energy supply, it is necessary to substantially increase the worldwide biomass energy utilization. The biomass waste is a potentially and interesting as energy raw material. It is one of alternative programe to change non-renewable energy to new and renewable energy.